2006
DOI: 10.1016/j.fishres.2005.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A Poisson and negative binomial regression model of sea turtle interactions in Hawaii's longline fishery

Abstract: Sea turtle interactions with the longline fishery in Hawaii have become a serious concern in recent years. Various measures, including a swordfish harvest ban, have been adopted to protect sea turtles. This study explores the factors and degree of sea turtle interactions with Hawaii's pelagic longline fishery, i.e. the production of undesirable outputs in the pursuit of an economic activity, in an analytical framework of rare events using the count data models for the period 1994-2003. The analysis was based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…This pattern holds in several different fisheries, such as pelagic longlines (Gilman et al 2006;Pradhan and Leung 2006;Sales et al 2010), drift gillnets (Gallaway 2001) and trammel nets (Cambiè 2011). The capture of sea turtles is rare (but see a different situation in Alfaro-Shigueto et al 2011 for small-scale fisheries).…”
Section: Discussionmentioning
confidence: 97%
“…This pattern holds in several different fisheries, such as pelagic longlines (Gilman et al 2006;Pradhan and Leung 2006;Sales et al 2010), drift gillnets (Gallaway 2001) and trammel nets (Cambiè 2011). The capture of sea turtles is rare (but see a different situation in Alfaro-Shigueto et al 2011 for small-scale fisheries).…”
Section: Discussionmentioning
confidence: 97%
“…We make use of estimates of turtle mortality (k ¼ 0.61) and fishery profits n ¼ 0.17 based on Pradhan and Leung [1].…”
Section: Simulations and Results In Two Scenariosmentioning
confidence: 99%
“…Hence, we have modeled sea turtle encounters in the Hawaii swordfish fishery as events governed by a Poisson process with intensity l (i.e., in a very short time period dt, the probability of an encounter with a sea turtle is l dt and for periods that do not overlap with each other, the probability of sea turtle encounter is independent). To estimate the value of l, we minimized the differences between the probabilities of sea turtle encounters generated by the Poisson process and the observed probabilities in Pradhan and Leung [1], essentially employing a non-linear least squares optimization procedure.…”
Section: Sea Turtle Encountersmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature suggests that the negative binomial is often a reasonable probability distribution for analyzing catch data because these data often exhibit over-dispersion (Claramunt et al, 2009;Clark, 1974;Power and Moser, 1999;Pradhan and Leung, 2006;Ward and Myers, 2005). Additionally, preliminary analysis that also involved testing the Poisson and geometric distributions indicated that assuming the negative binomial probability distribution provided the best fit to the observed data.…”
Section: Discussionmentioning
confidence: 99%